2021
DOI: 10.1007/s43545-021-00199-2
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between scholarship programs and higher education

Abstract: This study explores the effect of non-government scholarship programs on students' pursuit of higher education at the graduate and postgraduate level in Bangladesh. The study employed a self-administered questionnaire. It also explored general information about educational scholarships and determined the demographic profile of respondents within respective scholarship programs while pursuing higher education at the university level. The study's respondents comprised 330 students from different public universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a correlation investigation, Bliven and Jungbauer (2021) established that student motivation, self-determination, and persistence were positively related to student recognition programmes, acknowledging the students' efforts and other achievements in university. In addition, Rana, et al (2021) argued that scholarships enhanced the quality and standards of education among the scholarship recipients and further recommended that some scholarship programmes were less holistic, which may not be able to cover the whole expenses of the students. In a recent empirical investigation, Mulyaningsih, et al (2022), found that in Indonesia, large-scale targeted government scholarships had a very strong impact on students' performance, in particular, those who were least privileged and lived lives in poor conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a correlation investigation, Bliven and Jungbauer (2021) established that student motivation, self-determination, and persistence were positively related to student recognition programmes, acknowledging the students' efforts and other achievements in university. In addition, Rana, et al (2021) argued that scholarships enhanced the quality and standards of education among the scholarship recipients and further recommended that some scholarship programmes were less holistic, which may not be able to cover the whole expenses of the students. In a recent empirical investigation, Mulyaningsih, et al (2022), found that in Indonesia, large-scale targeted government scholarships had a very strong impact on students' performance, in particular, those who were least privileged and lived lives in poor conditions.…”
Section: Literature Reviewmentioning
confidence: 99%